Improved Poincaré inequalities in fractional Sobolev spaces - Drelichman, Irene (2018)
We obtain improved fractional Poincaré and Sobolev-Poincaré inequalities including powers of the distance to the boundary in bounded John, s-John, and Hölder-α domains, and discuss their optimality.